Enhanced Growth of Influenza Vaccine Seed Viruses in Vero Cells Mediated by Broadening the Optimal pH Range for Virus Membrane Fusion - Murakami, Shin (American Society for Microbiology, 2012)
Vaccination is one of the most effective preventive measures to combat influenza. Prospectively, cell culture-based influenza vaccines play an important role for robust vaccine production in both normal settings and urgent situations, such as during the 2009 pandemic. African green monkey Vero cells are recommended by the World Health Organization as a safe substrate for influenza vaccine production for human use. However, the growth of influenza vaccine seed viruses is occasionally suboptimal in Vero cells, which places limitations on their usefulness for enhanced vaccine production. Here, we present a strategy for the development of vaccine seed viruses with enhanced growth in Vero cells by changing an amino acid residue in the stem region of the HA2 subunit of the hemagglutinin (HA) molecule. This mutation optimized the pH for HA-mediated membrane fusion in Vero cells and enhanced virus growth 100 to 1,000 times in the cell line, providing a promising strategy for cell culture-based influenza vaccines.